IMPROVING THE STUDENTS’ SPEAKING PRACTICE IN DESCRIBING PEOPLE BY USING CONTEXTUALIZED CARD GAME - Muslichatun, Indah (Language Circle: Journal of Language and Literature, 2013)
Students often had problems to describe someone in English. The basic problem is the lack of practice. The students needed sufficient, fun and easy practice which would make them enthusiastic to do it. Therefore, I proposed the use of contextualized card game to improve the students’ speaking practice in describing people. I used classroom-action research to investigate how the use of contextualized card game can improve the students’ speaking practice in describing people. By implementing the game, the frequency of the students to describe people increased in cycle 2, ranging from 6.3 % up to 87.5 % compared to one in cycle 1. The students felt fun, enthusiastic, and confident as they were practicing speaking in groups while playing game and the object of description was within their knowledge. Besides, they described people better than before because in playing the game they learned from their friends and the teacher had facilitated them with sufficient and step-by step exercises. Further, the average score of the test improved from 74 in pre-cycle to 79 in cycle 1 and 83 in cycle 2. Thus, the use of contextualized card game can improve the students’ speaking practice.